Vivências da gravidez de adolescentes - Angela Maria Drumond Lage (2008)
The high incidence of teenage pregnancy has motivated studies about its repercussions inthe life of the adolescent girls, especially in their education, in the construction ofeconomical independence and in their social relationships, especially in the family.Considering this scenario, the study had the objective to analyze the occurrence and theconsequences of teenage pregnancy, recognizing the girls demands and needs for theexercise of their sexuality. It was adopted the qualitative method and the theoreticalreferences of the historical-dialectical materialism in the methodological path. The subjectsof this research were eighteen pregnant girls, aged from 13 to 19, identified using the dataof the SISPRENATAL in four Basic Health Units in the city of Patrocínio, Minas Gerais,Brazil. Individual interviews with semi-structured scrip were used to collect data. Theinterviews were done by the researcher in the houses of the pregnant girls after thesigning of the TCLE by the teenagers and their responsibles, when the girls were under 18years old. Discourse analysis oriented by the authors Fiorin and Savioli (1997) and Orlandi(1999) was used to analyze the data. This technique made it possible to recognize themeaning of what is explicit and implicit in the discourse in concrete contexts of life of thepregnant teenagers in the study. The discourse analysis resulted in the construction offour main thematic categories: feeling of lack of protection, pregnancy as a change of life,pregnancy as a life realization and expectations towards the future. The feeling of lack ofprotection was expressed in the reports of the teenagers when they associate thediscovery of the pregnancy with anxiety, fear and insecurity regarding the reaction of theparents, school mates and boyfriends or partners. Feelings of solitude and helplessnessresulting of the separation of the family and feelings of not fitting in when it comes to loverelationships and the social helplessness are also associated with this category. Thefeelings associated to pregnancy as a change of life emerged with the representation ofthe pregnancy as a desired phenomenon to some of the adolescents, while, to other girls,pregnancy was seen as something inevitable when one experiences sexuality. In thiscategory there were also feelings of ambivalence of conflicts related to the discovery andthe living of the pregnancy. The feelings associated to the pregnancy as a life realizationappeared in the reports related to the conquering of a dream to some of the adolescentswhile, to others, motherhood was associated to a greater responsibility in life and to apossibility of concretization of their life project. The expectations regarding the future wererevealed when the pregnancy was associated to a factor that would increase their ability toface difficulties, while other girls see the pregnancy as a factor that would make their lifeprojects more difficult to achieve. The study made it possible to know the variousperceptions and conflicts lived by the pregnant adolescents, reflecting the complexity andthe heterogeneity of the pregnancy in the life of the adolescent girls. This study shallcontribute to the elaboration of strategies and the implementation of actions that attendthe needs of the adolescents when it comes to sexual education, involving the educationalformation, the family support, the restructuring of the health services, the permanenteducation of the health and education professionals so that the access to information andto services is assured to all teenagers.